Análisis del beneficio fiscal a favor de la familia en los tributos cedidos en la España de las autonomías: periodo 2000-2015 - Náñez Alonso, Sergio (2018)
In the present article, the tax benefits present in the taxes assigned to the Spanish autonomous communities are analyzed; centering the study on those established in favor of the family. Initially, the analysis of the tax benefit carried out by other authors is studied. The concept of fiscal benefit is addressed, as well as the effects that derive from its establishment: equity, equal treatment and monetary allocation in the regulatory laws of each autonomous community and in its annual budgets. This is necessary in order to be able to carry out a qualitative and quantitative analysis in the period under study, from 2000 to 2015. After that, it is also exposed how the tax benefits established in the autonomous communities generate inequalities between citizens in the same event or situation. We analyze qualitatively and quantitatively the differences generated, as well as the allocation in euros per inhabitant, year and autonomous community. Once the analysis described above has been carried out, we can show the great difference that exists between the autonomous communities when it comes to establishing tax benefits in favor of the family; establishing differences between territories and leaving inequality in the allocation visible through tax benefits in euros per inhabitant, year and autonomous community.